Kuantan clay subgrade stabilization by using oil palm empty fruit brunches (OPEFB) ash mixed with Portland cement as stabilizer - Peter , Meredan (2012)
Stabilization is the process of blending and mixing materials with a soil to improve certain properties of the soil. This research is to study the relationship of Oil Palm Empty Fruit Brunches (OPEFB) ash mixed with Portland cements. The mixed additives between OPEFB ash and Portland cement according to ratio 2: 1 (3, 6 and 9 percent of OPEFB ash and mixed with 1.5, 3 and 4.5 percent Portland cement) for every of soil sample preparation. Clay soils are taken from Kuantan area (coordinate N 03'36.604' E 103' 19.322'). This thesis covered the engineering properties of soil sample such as sieve analysis, specific gravity, moisture content, Atterberg limit and standardproctor test. Meanwhile, for strength of soil it was covered by the California Bearing Ratio (CBR) test. The Kuantan clay soils can be classified as a kind of soils are highly compressible and have low strength. Maximum moisture content found in every percent of soil in Proctor test had used to prepare for California Bearing Ratio (CBR) test. The laboratory result show that the strength gain in stabilization mainly depends on two additives content and molding water content.